Modification method for coating tannic acid and polyether amine on surface of carbon fiber, product and application
By coating tannin acid and polyetheramine on the surface of the carbon fiber, the phenol-amine co-deposition method is used to solve the problem of insufficient binding force between the carbon fiber and the matrix, and the strength and toughness of the composite material are significantly improved.
Patent Information
- Application Number
- CN202510055211.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
AI Technical Summary
The non-polarity and wettability of the carbon fiber surface lead to a weak bonding force with the matrix, limiting the improvement of the strength and toughness of the composite material.
By coating tannin acid and polyetheramine on the carbon fiber surface, these substances are introduced by phenol-amine co-deposition method to improve the activity and compatibility of the carbon fiber surface, thereby enhancing the binding force with the composite matrix.
The interlayer shear strength and lateral tensile strength of the composite material are significantly improved, and the interface interaction between carbon fiber and epoxy resin is enhanced.
Smart Images

Figure CN119859917A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon fiber interface modification, and particularly relates to a modification method, product and application of coating tannic acid and polyetheramine on the surface of carbon fiber. Background Art
[0002] As a high-strength, low-density, high-modulus ratio fiber-reinforced material, carbon fiber can reinforce epoxy resin to improve the elastic modulus of the material. In recent years, with the innovation of technology, various industries, represented by aerospace, automobiles, and sports products, have put forward higher requirements for the materials used. Since carbon fiber has good wear resistance, heat resistance, acid and alkali resistance, and electrical and thermal conductivity, it has become an important reinforcing material in high-end application fields. Due to the non-polarity and poor wettability of the carbon fiber surface, the bonding force between it and the matrix is weak, making it difficult to achieve effective load transfer, thereby limiting the improvement of its strength and toughness. In order to solve this problem, the roughness and active groups of the carbon fiber surface can be increased through surface modification, thereby improving its compatibility with other materials, thereby enhancing the bonding force between it and the composite matrix, and then improving the strength of the composite material.
[0003] Wang et al. studied the use of tannic acid-aminopropyltriethoxysilane (APTES) to modify polyvinylidene fluoride (PVDF) membranes to achieve oil-water separation. Tannic acid, as a natural polymer, has good biocompatibility and modification effect, and can effectively enhance the hydrophilicity and anti-fouling ability of the membrane. Yang et al. modified the PVDF membrane by co-deposition in an aqueous buffer solution containing plant-based phenol gallic acid and amino-terminated aminopropyltriethoxysilane. This method changes the properties of the membrane from typical hydrophobicity to high hydrophilicity. Enhancing the hydrophilicity of the membrane can improve its ability to interact with water, thereby improving the filtration performance of the membrane and the oil-water separation efficiency. Liu et al. used a low-cost and easy-to-prepare modification method of catechol and polyethyleneimine to design a multifunctional water purification filtration process. As an important organic compound, catechol has good chemical stability and antioxidant properties. Polyethyleneimine increases the mechanical strength and hydrophilicity of the membrane, which improves the performance of this nanocomposite membrane in the water treatment process.
[0004] Although there are some reports on the application of tannic acid and polyetheramine, there is a lack of reports on a phenol-amine co-deposition modification method in the prior art on the modification method of carbon fiber, and there are few studies on the application of tannic acid (TA) and polyetheramine (PEA) coated carbon fiber in composite materials. Therefore, it is of great significance to study a modification method of tannic acid and polyetheramine coated carbon fiber to improve the performance of composite materials. Summary of the invention
[0005] The purpose of the present invention is to provide a metal polyphenol network coated carbon fiber and a preparation method and application thereof in order to overcome the shortcomings of the prior art. The preparation method of the present invention has mild conditions, high modification efficiency and strong versatility. The obtained TA-PEA coated carbon fiber reinforced composite material has improved interlaminar shear strength and transverse tensile strength.
[0006] In one aspect, the present invention provides a modification method for coating tannic acid and polyetheramine on the surface of carbon fiber, the method comprising the following steps:
[0007] Step 1: Desizing the carbon fiber to obtain desizing carbon fiber; preferably, acetone desizing is used, and 1-3 parts of carbon fiber and 5-10 parts of acetone are taken according to the mass ratio. The acetone desizing temperature is 68°C-90°C, and the desizing time is 48-96h; the drying temperature is 60-90°C, and the drying time is 3-6h.
[0008] Step 2: Prepare a Tris-HCl buffer solution with dilute hydrochloric acid and tris(hydroxymethyl)aminomethane, the pH of the solution being 7.5-8.9;
[0009] Step 3: adding tannic acid and polyetheramine to the Tris-HCl buffer solution of step 2, stirring to obtain a TA-PEA solution, wherein the mass ratio of tannic acid to polyetheramine is 1-4:1-4;
[0010] Step 4: Soak the desized carbon fiber in a TA-PEA solution, perform ultrasonic vibration, and then dry it to obtain carbon fiber coated with tannic acid and polyetheramine. The ultrasonic vibration frequency is 100-160kHz, and the vibration time is 5-7h.
[0011] A further improvement of this scheme is that the concentration of the dilute hydrochloric acid in step 2 is 0.1 mol / L.
[0012] A further improvement of the present scheme is that magnetic stirring is adopted in step 3, and the stirring time is 10-25 min.
[0013] A further improvement of this solution is that the mass ratio of tannic acid to polyetheramine in step 3 is 1:2.
[0014] In a further improvement of the present scheme, the drying temperature in step 4 is 50-70° C. and the drying time is 5-7 hours.
[0015] A further improvement of this solution is that the molecular weight of the polyetheramine in step 3 is 230-400.
[0016] In a further improvement of the present scheme, the mass volume ratio (g:ml) of the tannic acid and Tris-HCl buffer solution is 1:125-375; and the mass ratio of the carbon fiber to the tannic acid is 5:1.
[0017] A further improvement of this scheme, the modification method comprises the following steps:
[0018] Step 1: Put the carbon fiber into a Soxhlet extractor, pour in acetone, heat to 68°C, react for 48 hours, remove the sizing agent on the surface of the carbon fiber, take it out after the reaction, wash it with deionized water, and dry it to obtain the desized carbon fiber;
[0019] Step 2: Take 35 ml of 0.1 mol / L dilute hydrochloric acid, weigh 3.03 g of tris(hydroxymethyl)aminomethane, mix well, and then add deionized water to dilute to 500 ml to obtain a Tris-HCl buffer solution with a pH of 8.9;
[0020] Step 3: 2 g of tannic acid and 4 g of PEA were added to the above Tris-HCl buffer solution, and stirred with a magnetic stirrer for 20 min to obtain a solution with a mass ratio of TA to PEA of 1:2, and the molecular weight of the polyetheramine was 400;
[0021] Step 4: Soak the desized carbon fiber in TA-PEA solution and ultrasonically vibrate for 6 hours, then take it out at a frequency of 100 kHz, rinse it with deionized water, and then dry the carbon fiber at 60°C for 6 hours to obtain tannic acid and polyetheramine coated carbon fiber.
[0022] In a second aspect, the present invention provides a carbon fiber coated with tannic acid and polyetheramine obtained by the above modification method.
[0023] In a third aspect, the present invention provides an application of carbon fibers coated with tannic acid and polyetheramine in a composite material. The carbon fibers coated with tannic acid and polyetheramine are compounded with epoxy resin to prepare the composite material through a molding process.
[0024] The beneficial effects of the present invention are:
[0025] 1) The present invention obtains tannic acid and polyetheramine coated carbon fibers by optimizing components and parameters; the method introduces tannic acid and polyetheramine onto the surface of carbon fibers by using a phenol-amine co-precipitation method, and the preparation method has mild conditions, high modification efficiency and strong versatility.
[0026] 2) Coating tannic acid and polyetheramine on the surface of carbon fiber, by utilizing the abundant catechol groups in plant polyphenols, it can effectively react with amino polymers or organic matter containing amine groups to form phenol-amine small molecules. This process can be achieved through two main reaction pathways: Michael addition reaction and Schiff base reaction. In the Michael addition reaction, the nucleophilicity of the catechol group can react with the electron pairs in the amine group to form a new chemical bond. In the Schiff base reaction, the amine group reacts with the phenolic hydroxyl group to generate an imine intermediate, which then further reacts to form a more complex polymer structure. In addition, physical interactions (including hydrogen bonding, coordination, electrostatic interactions, cation-π interactions, π-π stacking, hydrophobic interactions, etc.) can not only assemble these groups into phenol-amine aggregates, but also promote the formed aggregates to adhere to the substrate surface and promote the growth of phenol-amine coatings. Therefore, plant polyphenols are mixed with amino polymers or organic matter containing amine groups to simulate the self-polymerization reaction of dopamine. A modified film can be obtained through a co-deposition strategy, thereby achieving the strong interfacial interaction required in carbon fiber reinforced epoxy resin composites, which can significantly improve the interlaminar shear strength and lateral tensile strength of the metal polyphenol network and carbon nanotube-coated carbon fiber reinforced epoxy resin. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is the morphology of the desized carbon fiber obtained in Example 1;
[0028] Figure 2 This is a morphology picture of the TA-PEA coated carbon fiber obtained in Example 1;
[0029] Figure 3 This is a scanning electron microscope image of the fracture surface of the desized carbon fiber reinforced composite material obtained in Example 2;
[0030] Figure 4 This is a scanning electron microscope image of the fracture surface of the TA-PEA coated carbon fiber reinforced composite material obtained in Example 2. DETAILED DESCRIPTION
[0031] In order to better understand the present invention, the technical solution of the present invention is described in detail with specific examples below, but the present invention is not limited thereto.
[0032] Other raw materials used in the present invention are all commercially available products.
[0033] First, the carbon fiber is desized. At low temperatures, the solubility of acetone decreases, resulting in residual slurry on the fiber surface, which affects the uniformity and effectiveness of subsequent coating. Higher temperatures will increase the solubility of acetone on the slurry in the carbon fiber, thereby more effectively removing the slurry, but too high a temperature will cause structural damage.
[0034] Short-term desizing will result in incomplete removal. Properly extending the desizing time can ensure that the sizing is fully removed, keep the carbon fiber surface clean, and help the subsequent coating reaction. However, desizing for too long will damage the fiber surface structure and affect its mechanical properties. Based on this, we selected an appropriate range.
[0035] Example 1
[0036] Step 1: Put 10g of carbon fiber into a Soxhlet extractor, pour in acetone, heat to 68°C, react for 48h, remove the sizing agent on the surface of the carbon fiber, take it out after the reaction, wash it with deionized water 5 times, and dry it to obtain desized carbon fiber;
[0037] Step 2: Weigh 35 ml of 0.1 mol / L dilute hydrochloric acid with a measuring cylinder, weigh 3.03 g of tris(hydroxymethyl)aminomethane with an electronic balance, mix them evenly in a beaker, and dilute to 500 ml with deionized water to obtain a Tris-HCl buffer solution with a pH of 8.9.
[0038] Step 3: 2 g of tannic acid (TA) and 4 g of polyetheramine (PEA) were weighed using an electronic balance and added to the above buffer solution, and stirred with a magnetic stirrer for 20 min to obtain a solution with a mass ratio of TA to PEA of 1:2, and the molecular weight of the polyetheramine was 400;
[0039] Step 4: Soak the desized carbon fiber in TA-PEA solution and ultrasonically oscillate for 6 hours, then take it out. The ultrasonic oscillation frequency is 100 kHz, rinse it with deionized water 5 times until the supernatant is colorless and transparent, and then place the carbon fiber in an electric blower drying oven and dry it at 60°C for 6 hours to obtain tannic acid and polyetheramine coated carbon fiber.
[0040] The morphology of the desized carbon fiber obtained in Example 1 is as follows: Figure 1 As shown, the morphology of the TA-PEA coated carbon fiber obtained in Example 1 is as follows Figure 2 shown.
[0041] The desizing carbon fiber and TA-PEA coated carbon fiber obtained in Example 1 were respectively compounded with epoxy resin E51, and a composite material was prepared by a flat vulcanizer through a molding process (the desizing carbon fiber and TA-PEA coated carbon fiber were 63% of the composite material volume fraction), and the interlaminar shear strength (ILSS) and transverse tensile strength of the composite material were tested. The method for preparing the composite material is: the desizing carbon fiber and the TA-PEA coated carbon fiber are fully impregnated in epoxy resin E51, respectively, to obtain two kinds of carbon fibers impregnated with resin, and the temperature of the flat vulcanizer is adjusted to 90°C by a temperature control system. In the process of heating the pressing plate to a specified temperature, the mold of the carbon fiber impregnated with resin is placed in a flat vulcanizer for preheating. When the temperature of the pressing plate reaches the specified temperature, the pressure is adjusted to 5MPa by a pressure control system, and the molding system is started, and maintained at 90°C and 5MPa for 1h. Then the temperature is adjusted to 120°C, the pressure is 10MPa, and maintained for 2h. Finally, the temperature is adjusted to 150°C, the pressure is still 10MPa, and maintained for 3h. After the molding is completed, the heating system is turned off, and the mixture is naturally cooled to room temperature under the pressure-maintaining state, and then demolded to obtain a composite material sample strip.
[0042] The interlaminar shear strength and transverse tensile strength of the desizing carbon fiber reinforced epoxy resin-based composite material of this embodiment are 50.9MPa and 26.44MPa respectively, and the interlaminar shear strength and transverse tensile strength of the TA-PEA coated carbon fiber reinforced epoxy resin-based composite material are 67.63MPa and 41.67MPa respectively. The carbon fiber treated with tannic acid and polyetheramine has a closer chemical bond with the resin as the number of surface oxygen-containing groups increases, which improves the interface performance of the composite material, and the interlaminar shear strength and transverse tensile strength are increased.
[0043] Example 2
[0044] Step 1: Put 10g of carbon fiber into a Soxhlet extractor, pour in acetone, heat to 68°C, react for 48h, remove the sizing agent on the surface of the carbon fiber, take it out after the reaction, wash it with deionized water 5 times, and dry it to obtain desized carbon fiber;
[0045] Step 2: Weigh 35 ml of 0.1 mol / L dilute hydrochloric acid with a measuring cylinder, weigh 3.03 g of tris(hydroxymethyl)aminomethane with an electronic balance, mix them evenly in a beaker, and dilute to 500 ml with deionized water to obtain a Tris-HCl buffer solution with a pH of 8.9.
[0046] Step 3: Use an electronic balance to weigh 2 g of tannic acid (TA) and 0.5 g of PEA solution, add them to the above buffer solution, and stir with a magnetic stirrer for 20 minutes to obtain a solution with a mass ratio of TA to PEA of 4:1, and the molecular weight of the polyetheramine is 400.
[0047] Step 4: Soak the desized carbon fiber in TA-PEA solution and ultrasonically oscillate for 6 hours, then take it out at a frequency of 100 kHz, rinse it with deionized water 5 times until the supernatant is colorless and transparent, and then place the carbon fiber in an electric blast drying oven and dry it at 60°C for 6 hours to obtain tannic acid and polyetheramine coated carbon fiber.
[0048] The desizing carbon fiber and TA-PEA coated carbon fiber obtained in Example 1 were respectively compounded with epoxy resin E51, and a composite material was prepared by a flat vulcanizer through a molding process (the desizing carbon fiber and TA-PEA coated carbon fiber were 63% of the composite material volume fraction), and the interlaminar shear strength (ILSS) and transverse tensile strength of the composite material were tested. The method for preparing the composite material is: the desizing carbon fiber and the TA-PEA coated carbon fiber are fully impregnated in epoxy resin E51, respectively, to obtain two kinds of carbon fibers impregnated with resin, and the temperature of the flat vulcanizer is adjusted to 90°C by a temperature control system. In the process of heating the pressing plate to a specified temperature, the mold of the carbon fiber impregnated with resin is placed in a flat vulcanizer for preheating. When the temperature of the pressing plate reaches the specified temperature, the pressure is adjusted to 5MPa by a pressure control system, and the molding system is started, and maintained at 90°C and 5MPa for 1h. Then the temperature is adjusted to 120°C, the pressure is 10MPa, and maintained for 2h. Finally, the temperature is adjusted to 150°C, the pressure is still 10MPa, and maintained for 3h. After the molding is completed, the heating system is turned off, and the mixture is naturally cooled to room temperature under the pressure-maintaining state, and then demolded to obtain a composite material sample strip.
[0049] The scanning electron microscope image of the fracture surface of the desizing carbon fiber reinforced composite material obtained in Example 2 is as follows: Figure 3 The scanning electron microscope image of the fracture surface of the TA-PEA coated carbon fiber reinforced composite material is shown in Figure 4 shown.
[0050] The interlaminar shear strength and transverse tensile strength of the TA-PEA coated carbon fiber reinforced epoxy resin-based composite material of this embodiment are 65.55 MPa and 35.57 MPa, respectively.
[0051] Example 3
[0052] Step 1: Put 10g of carbon fiber into a Soxhlet extractor, pour in acetone, heat to 68°C, react for 48h, remove the sizing agent on the surface of the carbon fiber, take it out after the reaction, wash it with deionized water 5 times, and dry it to obtain desized carbon fiber;
[0053] Step 2: Weigh 35 ml of 0.1 mol / L dilute hydrochloric acid with a measuring cylinder, weigh 3.03 g of tris(hydroxymethyl)aminomethane with an electronic balance, mix them evenly in a beaker, and dilute to 500 ml with deionized water to obtain a Tris-HCl buffer solution with a pH of 8.9.
[0054] Step 3: Use an electronic balance to weigh 2 g of tannic acid (TA) and 2 g of PEA solution, add them to the above buffer solution, and stir with a magnetic stirrer for 20 minutes to prepare a TA-PEA solution with a mass ratio of TA to PEA of 1:1, and the molecular weight of the polyetheramine is 400.
[0055] Step 4: Soak the desized carbon fiber in TA-PEA solution and ultrasonically oscillate for 6 hours, then take it out and dry it. The ultrasonic oscillation frequency is 100 kHz. Rinse it with deionized water for 5 times until the supernatant is colorless and transparent. Then place the carbon fiber in an electric blast drying oven and dry it at 60°C for 6 hours to obtain tannic acid and polyetheramine coated carbon fiber.
[0056] The composite material sample strip was obtained by using the same process as in Example 1, using a flat plate vulcanizer to prepare the composite material through a molding process.
[0057] The interlaminar shear strength and transverse tensile strength of the TA-PEA coated carbon fiber reinforced epoxy resin-based composite material of this embodiment are 56.51 MPa and 29.30 MPa, respectively.
[0058] Example 4
[0059] The difference from Example 1 is that, in step 3: 2 g of tannic acid (TA) and 8 g of PEA solution are weighed with an electronic balance and added to the above buffer solution, and stirred with a magnetic stirrer to prepare a TA-PEA solution with a mass ratio of TA to PEA of 1:4.
[0060] The interlaminar shear strength and transverse tensile strength of the TA-PEA coated carbon fiber reinforced epoxy resin-based composite material of this embodiment are 57.80 MPa and 28.02 MPa, respectively.
[0061] Based on Examples 1-4, it can be seen that when the mass ratio of TA to PEA is 1:2, the performance of the obtained composite material is optimal.
[0062] Example 5
[0063] Step 1: Put 10g of carbon fiber into a Soxhlet extractor, pour in acetone, heat to 68°C, react for 48h, remove the sizing agent on the surface of the carbon fiber, take it out after the reaction, wash it with deionized water 5 times, and dry it to obtain desized carbon fiber;
[0064] Step 2: Weigh 35 ml of 0.1 mol / L dilute hydrochloric acid with a measuring cylinder, weigh 3.03 g of tris(hydroxymethyl)aminomethane with an electronic balance, mix them evenly in a beaker, and dilute to 500 ml with deionized water to obtain a Tris-HCl buffer solution with a pH of 8.9.
[0065] Step 3: Weigh 2 g of tannic acid (TA) using an electronic balance and add it to the above buffer solution. Stir with a magnetic stirrer for 20 minutes to prepare a TA solution.
[0066] Step 4: Soak the desized carbon fiber in TA solution and ultrasonically oscillate for 6 hours, then take it out. The ultrasonic oscillation frequency is 100 kHz, rinse it with deionized water 5 times until the supernatant is colorless and transparent, and then place the carbon fiber in an electric blast drying oven and dry it at 60°C for 6 hours to obtain tannic acid-coated carbon fiber.
[0067] The obtained TA coated carbon fiber was compounded with epoxy resin E51 respectively, and a composite material (TA coated carbon fiber is 63% of the volume fraction of the composite material) was prepared by a flat vulcanizer through a molding process, and the interlaminar shear strength (ILSS) and transverse tensile strength of the composite material were tested. The method for preparing the composite material is: the TA coated carbon fiber is fully impregnated in epoxy resin E51 to obtain resin-impregnated carbon fiber, the temperature of the flat vulcanizer is adjusted to 90°C by a temperature control system, and in the process of heating the pressing plate to a specified temperature, the mold wrapped with the resin-impregnated carbon fiber is placed in a flat vulcanizer for preheating, and when the pressing plate temperature reaches the specified temperature, the pressure is adjusted to 5MPa by a pressure control system, and the molding system is started, and maintained at 90°C and 5MPa for 1h. Then adjust the temperature to 120°C and the pressure to 10MPa, and maintain for 2h. Finally, adjust the temperature to 150°C, the pressure is still 10MPa, and maintain for 3h. After the molding is completed, turn off the heating system, cool naturally to room temperature under the pressure holding state, demould, and obtain a composite sample strip.
[0068] The interlaminar shear strength and transverse tensile strength of the coated carbon fiber reinforced epoxy resin-based composite material of this embodiment are 52.01 MPa and 27.99 MPa, respectively.
[0069] Example 6
[0070] Step 1: Put 10g of carbon fiber into a Soxhlet extractor, pour in acetone, heat to 68°C, react for 48h, remove the sizing agent on the surface of the carbon fiber, take it out after the reaction, wash it with deionized water 5 times, and dry it to obtain desized carbon fiber;
[0071] Step 2: Weigh 35 ml of 0.1 mol / L dilute hydrochloric acid with a measuring cylinder, weigh 3.03 g of tris(hydroxymethyl)aminomethane with an electronic balance, mix them evenly in a beaker, and dilute to 500 ml with deionized water to obtain a Tris-HCl buffer solution with a pH of 8.9.
[0072] Step 3: Weigh 4 g of PEA using an electronic balance and add it to the above buffer solution. Stir with a magnetic stirrer for 20 minutes to obtain a PEA solution with a molecular weight of 400 polyetheramine.
[0073] Step 4: Soak the desized carbon fiber in the PEA solution and ultrasonically oscillate for 6 hours, then take it out at a frequency of 100 kHz, rinse it with deionized water 5 times until the supernatant is colorless and transparent, and then place the carbon fiber in an electric blast drying oven and dry it at 60°C for 6 hours to obtain polyetheramine-coated carbon fiber.
[0074] The obtained PEA coated carbon fiber was compounded with epoxy resin E51 respectively, and a composite material (PEA coated carbon fiber was 63% of the composite material volume fraction) was prepared by a flat vulcanizer through a molding process, and the interlaminar shear strength (ILSS) and transverse tensile strength of the composite material were tested. The method for preparing the composite material is as follows: PEA coated carbon fiber is fully impregnated in epoxy resin E51 to obtain resin-impregnated carbon fiber, the temperature of the flat vulcanizer is adjusted to 90°C by a temperature control system, and in the process of heating the pressing plate to a specified temperature, the mold wrapped with the resin-impregnated carbon fiber is placed in a flat vulcanizer for preheating, and when the pressing plate temperature reaches the specified temperature, the pressure is adjusted to 5MPa by a pressure control system, and the molding system is started and maintained at 90°C and 5MPa for 1h. Then the temperature is adjusted to 120°C and the pressure is 10MPa, and maintained for 2h. Finally, the temperature is adjusted to 150°C, and the pressure is still 10MPa, and maintained for 3h. After the molding is completed, the heating system is turned off, and the pressure is naturally cooled to room temperature under the pressure holding state, and the mold is demolded to obtain a composite sample strip.
[0075] The interlaminar shear strength and transverse tensile strength of the PEA-coated carbon fiber reinforced epoxy resin-based composite material of this embodiment are 53.44 MPa and 28.05 MPa, respectively.
[0076] By comparing Examples 1, 5, and 6, it can be found that the interaction between tannic acid and polyetheramine promotes the coating on the surface of carbon fiber.
[0077] Example 7
[0078] The difference from Example 1 is that in step 2, a Tris-HCl buffer solution with a pH of 7.5 is obtained.
[0079] Example 8
[0080] The difference from Example 1 is that in step 2, a Tris-HCl buffer solution with a pH of 6.8 is obtained.
[0081] Example 9
[0082] The difference from Example 1 is that in step 2, a Tris-HCl buffer solution with a pH of 9.1 is obtained.
[0083] The pH value of 7-9 can be adjusted by adjusting the amount of diluted hydrochloric acid added.
[0084] By comparing and observing the sample structures of Examples 1, 7, 8, and 9, it is found that Example 8 does not achieve TA-PEA coating of desized carbon fibers. Under acidic conditions, the dissociation degree of tannic acid is reduced, and it exists in a relatively stable form in the solution, but at the same time this also limits its reactivity, so that it cannot effectively react with polyetheramine, affecting the formation of the coating. Under low pH conditions, the amino group of polyetheramine is protonated to form positively charged ammonium ions. Although this can increase its solubility and hydrophilicity, the excessive degree of protonation inhibits its reactivity with tannic acid, resulting in a decrease in the coating effect. In addition, low pH causes the carbon fiber surface to carry more positive charges, resulting in a weakened interaction between it and polyetheramine. If the carbon fiber is poorly combined with polyetheramine, the coating effect will be affected. At the same time, at a lower pH value, the reaction kinetics between tannic acid and polyetheramine are inhibited, affecting the reaction rate, resulting in uneven or unstable formation of the coating layer.
[0085] Although TA-PEA coating was achieved in Examples 7 and 9, the coating effect of Example 9 was extremely poor. At higher pH values, the degree of dissociation of tannic acid will increase, resulting in it carrying more negative charges, which will affect its interaction with the carbon fiber surface, thereby affecting the coating effect. High pH will inhibit the reactivity of tannic acid, reduce its reaction efficiency with polyetheramine, and thus affect the ability to form a stable coating layer. The amino group of polyetheramine remains in a deprotonated state under high pH conditions, thereby enhancing its hydrophilicity and solubility, which helps its interaction with tannic acid. However, too high a pH value will change its chemical properties, resulting in reduced reactivity. And at higher pH, the molecular structure and charge characteristics of polyetheramine will affect its adsorption capacity on the carbon fiber surface, thereby affecting the uniformity and effectiveness of the coating. In addition, the higher pH value causes the carbon fiber surface to carry more negative charges, thereby affecting its adsorption behavior with the positively charged polyetheramine. This change in charge characteristics will lead to a decrease in adsorption efficiency, thereby affecting the final coating effect.
[0086] Example 9
[0087] The difference from Example 1 is that the ultrasonic oscillation frequency is 50 kHz.
[0088] Example 10
[0089] The difference from Example 1 is that the ultrasonic oscillation frequency is 160 kHz.
[0090] Embodiment 11
[0091] The difference from Example 1 is that the ultrasonic oscillation frequency is 250 kHz.
[0092] Through the obtained carbon fiber structure coated with tannic acid and polyetheramine, it was found that although coating was achieved, the coating effects of the products in Examples 9 and 11 were very poor. The lower ultrasonic oscillation frequency affects the dispersion of the product, and although high-frequency ultrasound can produce fine cavitation bubbles and generate smaller turbulence, which is suitable for more delicate mixing and dispersion, high-frequency ultrasound causes local temperature rise, which in some cases affects the stability and reactivity of tannic acid and polyetheramine. The appropriate ultrasonic oscillation frequency can produce larger cavitation bubbles, followed by strong liquid disturbance, which helps to improve the mixing uniformity of the solution, thereby enhancing the adsorption of tannic acid and polyetheramine on the carbon fiber surface.
[0093] Example 12
[0094] The difference from Example 1 is that the molecular weight of the polyetheramine used is 230.
[0095] Embodiment 13
[0096] The difference from Example 1 is that the molecular weight of the polyetheramine used is 2000.
[0097] By comparing the carbon fiber structures coated with tannic acid and polyetheramine obtained in Examples 1, 12, and 13, it is found that when the molecular weight is 230 and 400, the coating effect is good. The polyetheramine molecules with lower molecular weight are relatively small and are more likely to penetrate the microscopic pores of carbon fibers, enhancing their adsorption capacity. When the molecular weight of polyetheramine is low, the surface activity is large, the movement of the molecules in the solution is more flexible, and it can better interact with the carbon fiber surface to promote the adsorption of tannic acid. However, the coating effect of the product obtained in Example 13 is not good, which should be because the polyetheramine with higher molecular weight forms larger aggregates when combined with carbon fibers, affecting its effective coating.
[0098] The raw materials listed in the present invention, as well as the upper and lower limits and interval values of the raw materials of the present invention, and the upper and lower limits and interval values of the process parameters can all realize the present invention, and the embodiments are not listed one by one here.
[0099] The above is only a preferred embodiment of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and changes can be made without departing from the principle of the present invention, and these improvements and changes are also regarded as the protection scope of the present invention.
Claims
1. A modification method for coating tannic acid and polyetheramine on the surface of carbon fiber, characterized in that: The method comprises the following steps: Step 1: Desizing the carbon fiber to obtain desizing carbon fiber; Step 2: Prepare a Tris-HCl buffer solution with dilute hydrochloric acid and tris(hydroxymethyl)aminomethane, the pH of the solution being 7.5-8.9; Step 3: adding tannic acid and polyetheramine to the Tris-HCl buffer solution of step 2, stirring to obtain a TA-PEA solution, wherein the mass ratio of tannic acid to polyetheramine is 1-4:1-4; Step 4: soak the desized carbon fiber in a TA-PEA solution, perform ultrasonic vibration, and then dry it to obtain carbon fiber coated with tannic acid and polyetheramine. The ultrasonic vibration frequency is 100-160kHz and the vibration time is 5-7h.
2. The modification method of coating tannic acid and polyetheramine on the surface of carbon fiber according to claim 1, characterized in that: The concentration of dilute hydrochloric acid in step 2 is 0.1 mol / L.
3. The modification method of coating tannic acid and polyetheramine on the surface of carbon fiber according to claim 1, characterized in that: In step 3, magnetic stirring is used, and the stirring time is 10-25 minutes.
4. The modification method of coating tannic acid and polyetheramine on the surface of carbon fiber according to claim 1, characterized in that: In the step 3, the mass ratio of tannic acid to polyetheramine is 1:
2.
5. The modification method of coating tannic acid and polyetheramine on the surface of carbon fiber according to claim 1, characterized in that: The drying temperature in step 4 is 50-70° C. and the drying time is 5-7 hours.
6. The modification method of coating tannic acid and polyetheramine on the surface of carbon fiber according to claim 1, characterized in that: In step 3, the molecular weight of the polyetheramine is 230-400.
7. The modification method of coating tannic acid and polyetheramine on the surface of carbon fiber according to claim 1, characterized in that: The mass volume ratio (g:ml) of the tannic acid and Tris-HCl buffer solution is 1:125-375; the mass ratio of the carbon fiber to the tannic acid is 5:
1.
8. The modification method of coating tannic acid and polyetheramine on the surface of carbon fiber according to claim 1, characterized in that: The following steps are involved: Step 1: Put 10g of carbon fiber into a Soxhlet extractor, pour in acetone, heat to 68°C, react for 48h, remove the sizing agent on the surface of the carbon fiber, take it out after the reaction, wash it with deionized water, and dry it to obtain desized carbon fiber; Step 2: Take 35 ml of 0.1 mol / L dilute hydrochloric acid, weigh 3.03 g of tris(hydroxymethyl)aminomethane, mix well, and then add deionized water to dilute to 500 ml to obtain a Tris-HCl buffer solution with a pH of 8.9; Step 3: 2 g of tannic acid and 4 g of PEA were added to the above Tris-HCl buffer solution, and stirred with a magnetic stirrer for 20 min to obtain a solution with a mass ratio of TA to PEA of 1:2, and the molecular weight of the polyetheramine was 400; Step 4: Soak the desized carbon fiber in TA-PEA solution and ultrasonically vibrate for 6 hours, then take it out at a frequency of 100 kHz, rinse it with deionized water, and then dry the carbon fiber at 60°C for 6 hours to obtain tannic acid and polyetheramine coated carbon fiber.
9. Carbon fiber coated with tannic acid and polyetheramine obtained according to the modification method of claims 1-8.
10. The use of carbon fiber coated with tannic acid and polyetheramine in composite materials according to claim 9, characterized in that: The tannic acid and polyetheramine coated carbon fiber is compounded with epoxy resin and a composite material is prepared through a molding process.
Citation Information
Patent Citations
Carbon fiber surface polymerization modification method
CN110791963A
Sizing agent for bulletproof material as well as preparation method and application of sizing agent
CN119121628A